The Influence of Mindfulness Sport Performance Enhancement Training on Self-Confidence in Petanque Athletes - Elzas, Elzas Nurajab; Budiman, Ali; Rusmana, Ruslan; Sutiswo; Adiputra, Mulyana (Journal of Physical and Outdoor Education, 2024)
This research aims to determine the effect of mindfulness sport performance enhancement training on self-confidence in athletes of the sport of petanque. The research method used is the experimental method with a pre-test/post-test approach. The instrument used in this research is a questionnaire. The population used in this study consists of all the petanque athletes from the West Java training center, totaling 10 individuals. The sample used in this study is the petanque athletes from the West Java training center, also totaling 10 individuals. The sampling technique used is "saturation sampling." From the research results, it can be concluded that there is an influence of mindfulness sport performance enhancement training on the self-confidence of athletes in the sport of petanque.